2019
DOI: 10.14238/sp21.2.2019.96-101
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan rasio netrofil limfosit dengan hipertensi arteri pulmonal pada anak dengan penyakit jantung bawaan asianotik

Abstract: Latar belakang. Hipertensi arteri pulmonal (HAP) merupakan komplikasi yang sering terjadi penyakit jantung bawaan (PJB). Peningkatan tekanan vaskular paru disebabkan oleh disfungsi sel endotel paru yang ditandai oleh inflamasi perivaskular. Rasio neutrofil limfosit (RNL) merupakan salah satu penanda biologis inflamasi yang murah dan mudah dan berhubungan dengan penyakit jantung.Tujuan. Untuk mengetahui hubungan RNL dengan HAP pada anak dengan PJB asianotik.Metode. Penelitian potong lintang pada pasien anak usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…A similar number was also found in a study in the Netherlands, in which the incidence of PAH in adult CHD patients was found to be 4.2% [11]. Meanwhile, the research at RSUD Dr. Moewardi Surakarta showed that the incidence of PAH in children with acyanotic CHD was 56.7% [12].…”
Section: Discussionsupporting
confidence: 77%
“…A similar number was also found in a study in the Netherlands, in which the incidence of PAH in adult CHD patients was found to be 4.2% [11]. Meanwhile, the research at RSUD Dr. Moewardi Surakarta showed that the incidence of PAH in children with acyanotic CHD was 56.7% [12].…”
Section: Discussionsupporting
confidence: 77%